LEGAL POLITICS CHANGING A BUILDING CONSTRUCTION PERMIT (IMB) INTO BUILDING CONSTRUCTION APPROVAL (PBG) - Qurni Annamalia; Shinta Hadiyantina; Dewi Cahyandari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This research aims to analyze changes in the nomenclature of permits and approvals in simplifying licensing administration. This research also focuses on legal politics in changing the nomenclature of Building Construction Permits (IMB) to Building Construction Approvals (PBG) through the Job Creation Law. This licensing simplification effort focuses on eliminating administrative requirements and submitting technical requirements to more specific Government Regulations. In this context, it is necessary to conduct an in-depth study of the differences between Building Construction Approvals (PBG) and Building Construction Permits (IMB) from various aspects, including grammatical, philosophical, sociological and juridical, as well as their impact on the meaning of permits and approvals related to changes. in Government Regulations. As a result, the nomenclature of Building Construction Permit (IMB) was changed to Building Construction Approval (PBG). This research is normative legal research using a statutory approach. The legal politics of changing nomenclature is based on what objectives are to be achieved with the existing legal system; What method you feel is best to use to achieve this goal; When does the law need to be revised and in what way is the law changed; Can it be formulated in the form of a standard and established pattern, which can help in deciding the process of selecting goals and ways to achieve these goals well, as stated by Satjipto Raharjo? Based on the research results, the main difference between a Building Construction Permit (IMB) and a Building Construction Permit (PBG) lies in the method of use and the permit application stage before the construction process. IMB is a type of permit that must be obtained by the building owner before or during the construction process. On the other hand, PBG has a form of licensing regulation that regulates the procedures for how buildings must be erected. Keywords: Legal Politics; Building permit; Building Approval.